Eosinophil Progenitors in Patients With Non-Asthmatic Eosinophilic Bronchitis, Eosinophilic Asthma, and Normal Controls - Zhan, Chen; Xu, Rong; Li, Bizhou; Liu, Jiaxing; Liang, Wanqin; Zhang, Shengfang; Fang, Liman; Zhong, Shuxin; de Silva, S. Dushinka Shaniya Helen; Sivapalan, Dhinesan; Luo, Wei; Li, Jing; et al. (Frontiers in Immunology, 2022)
Objective: To explore the potential of in situ airway differentiation of eosinophil progenitors (EoPs) and hematopoietic progenitor cells (HPCs) in sputum and peripheral blood from patients with non-asthmatic eosinophilic bronchitis (NAEB), eosinophilic asthma (EA) and healthy controls (HC). Methods: Using flow cytometry, we enumerated sputum and blood HPCs and EoPs by in patients with NAEB (n=15), EA (n=15), and HC (n=14) at baseline. Patients with NAEB and EA were then treated for one month with budesonide (200ug, bid), or budesonide and formoterol (200/6ug, bid), respectively. HPCs and EoPs in both compartments were re-evaluated. Results: At baseline, NAEB and EA both had significantly greater numbers of sputum but not blood HPCs and EoPs (p<0.05) compared to HC. There were no differences between NAEB and EA. After one-month of inhaled corticosteroid (ICS) treatment, NAEB patients showed a significant improvement in cough symptoms but the attenuation of sputum HPC and EoP levels was not significant. Conclusions: NAEB patients have increased airway levels of HPCs and EoPs. One-month treatment with ICS did not fully suppress the level of EoPs in NAEB. Controlling in situ airway differentiation of EoPs may control airway eosinophilia and provide long-term resolution of symptoms in NAEB